Effect Of Electric Load On Steam Flow Rate At Steam Turbine As Generator - Dedi Wardianto; Marfizal; Sufiyanto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2022)
PT. Kurnia Batang Hari is a palm oil processing factory into palm oil. At PT KBHB there is a tool called “Steam Turbine Generator Type RB5” which functions as a power generator. This study aims to determine the effect of the load on the mass flow rate, turbine generator power, and determine the efficiency of the steam turbine generator. The research method is to take boiler and turbine data directly for 1 week. Get the enthalpy value from the steam table and can calculate based on the research objective. Based on the research conducted, it was found that the highest average flow rate on Wednesday was 3.48 kg/s. The highest generator power yield on Sunday is 1661 KW. The results of the calculation of the highest average generator efficiency on Sundays are 57.11%. Conclusion It can be seen that if the load on the turbine is getting bigger, then the mass flow rate of the steam will be even bigger and it also depends on the pressure of the steam entering and leaving the turbine. The average load of 1 week borne by the generator is 885 KW and the mass flow rate is 3.81 kg/s. The generator power produced during processing is an average of 1 week, which is 1600 KW. The average efficiency of the generator in 1 week is 55.52% on Sunday.